Implementasi E-Learning Berbasis TPACK sebagai Transformasi Pembelajaran Digital di Pondok Pesantren Nurul Yaqin Jember - Rizky Yanuarti; Hardiani Kusuma, Ajeng Pramesthy; Demiawan Rachmatta Putro Mudiono; Mawar Yoktaviya Putri Prayoto; D’ajeng Assyura Maharani Susanto; Fajar Yuda Setiawan; Firdaus Waridil Wishal (Fakultas Teknik, Universitas PGRI Banyuwangi, 2026)
Existing learning and administrative conditions at the Nurul Yaqin Islamic Boarding School in Jember are currently still entirely conventional, with low levels of digital literacy among teachers and students. Based on these issues faced by our partners, this community service program aims to accelerate the digital transformation of Islamic boarding school education through the implementation of an e-learning system based on the Technological Pedagogical Content Knowledge (TPACK) framework. The activity involved four key stages: needs assessment, training on digital tools (Google Classroom, Canva, Google Forms), implementation, and mentoring. The results showed that teachers’ digital competence increased from 20% to 100%, and students’ participation in e-learning activities rose from 40% to 90%. Moreover, the digital administration system, including QR code-based attendance and digital archiving, reduced administrative time by approximately 50%. This program contributes to the development of technology-integrated pedagogy in Islamic education, the strengathening of teachers’ digital competence and instructional innovation, and the promotion of sustainable digital transformation in pesantren-based education systems.